Patient-controlled analgesia compared with interval analgesic dosing for reducing complications in blunt thoracic trauma: a retrospective cohort study. Issue 12 (6th December 2012) - Asha, Stephen Edward; Curtis, Kate Anne; Taylor, Colman; Kwok, Allan
Abstract : Objectives: To determine if complications from blunt thoracic trauma are reduced with patient-controlled analgesia (PCA) compared with interval analgesic dosing given as needed. Secondary aims were to investigate the influence of PCA on hospital length of stay (LOS) and cost. Methods: In this retrospective cohort study, patients were identified using the hospital trauma registry and clinical information department. Data on analgesic method, outcomes and confounders were obtained from the medical record. Costing data were obtained from the case-mix department. The analysis used logistic regression for the primary outcome and a generalised linear model for the secondary outcomes to adjust for potential confounders. Results: 227 patients were included. In the PCA group, 17/52 (33%) patients had a complication compared with 26/175 (15%) in the interval dosing group. The adjusted odds for a complication in patients receiving PCA was not significantly different from the adjusted odds in those receiving interval dosing (OR=1.2, 95% CI 0.3 to 4.6, p=0.83). The median LOS was 8.9 days in the PCA group and 4.6 days in the interval dosing group. The adjusted LOS for patients receiving PCA was 10% shorter than those receiving interval dosing (relative difference 0.9, 95% CI 0.6 to 1.3, p=0.52). The median hospital cost was $A11 107 in the PCA group (IQR $A7520–$A15 744) and $A4511 (IQR $A2687–$A8248) in the interval dosing group. The adjusted total hospital costs for patients receiving PCA was 10% higher than for those receiving interval dosing (relative difference 1.1, 95% CI 0.8 to 1.5, p=0.44). Conclusions: PCA did not reduce complications, hospital LOS or costs compared with interval analgesic dosing.